Monitoring Pengelolaan Dana Desa di Desa Kesesirejo Kecamatan Bodeh Kabupaten Pemalang - Kowam Syaiful Kalam; R Slamet Santoso; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Village Fund itself is used to finance governance, community development, and community empowerment. Priority is given to community empowerment and development using village funds. In order to improve the welfare of rural communities, the quality of human life, and poverty alleviation, this provision is prioritized in financing development and community empowerment. The Central Government provides a sizable budget to Regional Governments, even increasing every year. Kesesirejo Village is a village in Bodeh District, Pemalang Regency, a village located in Central Java, which administratively receives Village Funds from the state expenditure budget from the central government. This study aims to describe monitoring in managing Village Funds in Kesesirejo Village, Bodeh District, Pemalang Regency and to analyze the obstacles faced by Village Fund managers in Kesesirejo Village, Bodeh District, Pemalang Regency. This study uses qualitative methods, data collection techniques with interviews, observation, and documentation, data sources using primary data and secondary data. The results of the study show that Monitoring of Village Fund Management in Kesesirejo Village, Bodeh District, Pemalang Regency has been good in terms of obedience, inspection, reports, accountability. However, there are still several monitoring sections that are not good internally and in human resources.